2017
DOI: 10.14358/pers.83.5.377
|View full text |Cite
|
Sign up to set email alerts
|

Identification Of Unpaved Roads in a Regional Road Network Using Remote Sensing

Abstract: An accurate inventory of unpaved road network length and condition within a county, state, or region is important for efficient use of resources to manage and maintain this critical transportation asset. Object-based classification techniques provide a cost-effective way to identify unpaved roads within a local agency's road network when the road type (i.e., paved versus unpaved) attribute is missing. We present a Trimble eCognition® algorithm using four band optical aerial imagery and object-based classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This study has proven the role of remote sensing in facilitating the review and evaluation of road conditions and significant reduction of field data and introduced visible methods more tangible and cheaper than methods such as radar and terrestrial scanning. Brooks et al (2017) distinguished paved roads from unpaved ones in a regional road network using remote sensing and four-lane UAV images and object-based classification. The results of this study proved the relationship between the number of bands and the accuracy of separation, classification, and segmentation of paved and unpaved roads.…”
Section: The Separation Of the Unpaved Roads And Prioritization Of Pa...mentioning
confidence: 99%
“…This study has proven the role of remote sensing in facilitating the review and evaluation of road conditions and significant reduction of field data and introduced visible methods more tangible and cheaper than methods such as radar and terrestrial scanning. Brooks et al (2017) distinguished paved roads from unpaved ones in a regional road network using remote sensing and four-lane UAV images and object-based classification. The results of this study proved the relationship between the number of bands and the accuracy of separation, classification, and segmentation of paved and unpaved roads.…”
Section: The Separation Of the Unpaved Roads And Prioritization Of Pa...mentioning
confidence: 99%
“…Their reliability, real-time, and implementation cost have some limits in application. The representative research works are as follows: Jokela et al used stereo cameras to monitor road conditions [26]; Nomura et al used acoustic equipment to measure the tire noise and identified the road condition by a neural network [27]; Alonso et al proposed an identification method based on a noise sensor and the support vector machine technology [28]; Paulo et al comprehensively used probability statistics and neural network to identify road types [29]; Brooks et al identified the unpaved roads by remote sensing technologies [30]; and Liu et al monitored the road levels through the engine speed [31]. These works play a role in promoting the realization of road identification technologies.…”
Section: Introductionmentioning
confidence: 99%